1977
DOI: 10.1083/jcb.72.1.104
|View full text |Cite
|
Sign up to set email alerts
|

Morphological changes of the adipose cell plasma membrane during lipolysis.

Abstract: Morphological changes of the plasma membrane in the white adipose cell associated with lipid mobilization were assessed qualitatively and quantitatively on freeze-fracture replicas of epididymal adipose tissue from fasted and from streptozotocin-diabetic rats. The number of plasma membrane invaginations and intramembranous particles were evaluated per square micrometer of membrane and per entire adipocyte. These two determinations show that the number per square micrometer (local concentration) of both structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
0
1

Year Published

1981
1981
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 16 publications
1
18
0
1
Order By: Relevance
“…Moreover, electron microscopy proved that fat cells in the EC are true adipocytes, provided with surface vesicles and continuous basal laminae, as generally described for adipocytes (Carpentier et al, 1977;Cinti et al, 1984;Rhodin, 1974).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Moreover, electron microscopy proved that fat cells in the EC are true adipocytes, provided with surface vesicles and continuous basal laminae, as generally described for adipocytes (Carpentier et al, 1977;Cinti et al, 1984;Rhodin, 1974).…”
Section: Discussionmentioning
confidence: 79%
“…Physicochemical properties of the alcianophilic ground substance in myxoid and cartilage areas most likely remain constant over time. By contrast, the volume of adipocytes can change significantly according to metabolic situations (Carpentier et al, 1977). Therefore, we speculate that the rigidity of the supporting organ can be adapted by controlling the metabolic state of the fat lobules encountered.…”
Section: Discussionmentioning
confidence: 95%
“…Still others, in the electron microscopic picture, observed a positive reaction for S100 protein in continuous type capillary endothelia in rat testis, while negative in fenestrated type endothelium [31]. Moreover, Carpentier [32] observed an increased amount of S100 protein positive vesicles in endothelial cells of adjacent capillaries during lipolysis. Since one of the major roles of endothelial cells is to transport bioactive substances from blood into the perivascular space, Iwanaga [28] suggested that S100 protein in the continuous type capillary endothelium may be involved in the transport of fatty acids and/or other substances.…”
Section: Discussionmentioning
confidence: 93%
“…This may be because of the technical difficulty of examining these cells by electron microscopy owing to their very high lipid content. Recently, Carpentier et al (8,9), and Jarett et al (26) examined the morphology of adipocytes of young rat s during lipolysis by the freeze-fracture method and scanning electron microscopy. Our previous papers desribed the morphology of isolated adipocytes examined by transmission and scanning electron microscopies (18,19).…”
mentioning
confidence: 99%
“…For freeze-fracturing electron microscopy, small pieces of adipose tissue were fixed for 2 hr in 2.5% glutaraldehyde solution in phosphate buffer, pH 7.4, and then treated for at least 30 min with 20% glycerol in Krebs-Ringer phosphate buffer. They were then rapidly frozen in liquid nitrogen, fractured and shadowed in an FD-2A apparatus (Eiko Engineering Co.) as described by Carpentier et al (9). Adipocytes were difficult to freeze-fracture.…”
mentioning
confidence: 99%